Mutations in FKBP10 Cause Recessive Osteogenesis Imperfecta and Bruck Syndrome - ELÇİOĞLU, HURİYE NURSEL (WILEY, 2011)
Osteogenesis imperfecta (OI) is a genetic disorder of connective tissue characterized by bone fragility and alteration in synthesis and posttranslational modification of type I collagen. Autosomal dominant OI is caused by mutations in the genes (COL1A1 or COL1A2) encoding the chains of type I collagen. Bruck syndrome is a recessive disorder featuring congenital contractures in addition to bone fragility; Bruck syndrome type 2 is caused by mutations in PLOD2 encoding collagen lysyl hydroxylase, whereas Bruck syndrome type 1 has been mapped to chromosome 17, with evidence suggesting region 17p12, but the gene has remained elusive so far. Recently, the molecular spectrum of OI has been expanded with the description of the basis of a unique posttranslational modification of type 1 procollagen, that is, 3-prolyl-hydroxylation. Three proteins, cartilage-associated protein (CRTAP), prolyl-3-hydroxylase-1 (P3H1, encoded by the LEPRE1 gene), and the prolyl cis-trans isomerase cyclophilin-B (PPIB), form a complex that is required for fibrillar collagen 3-prolyl-hydroxylation, and mutations in each gene have been shown to cause recessive forms of OI. Since then, an additional putative collagen chaperone complex, composed of FKBP10 (also known as FKBP65) and SERPINH1 (also known as HSP47), also has been shown to be mutated in recessive OI. Here we describe five families with OI-like bone fragility in association with congenital contractures who all had FKBP10 mutations. Therefore, we conclude that FKBP10 mutations are a cause of recessive osteogenesis imperfecta and Bruck syndrome, possibly Bruck syndrome Type 1 since the location on chromosome 17 has not been definitely localized. (C) 2011 American Society for Bone and Mineral Research.
Keywords: OSTEOGENESIS IMPERFECTA; BRUCK SYNDROME; FKBP10 (ALSO KNOWN AS FKBP65); BRITTLE BONE DISEASE; COLLAGEN; CONGENITAL JOINT CONTRACTURES; TELOPEPTIDE LYSYL HYDROXYLASE; FK506-BINDING PROTEIN; CROSS-LINKING; ENDOPLASMIC-RETICULUM; BONE FRAGILITY; I COLLAGEN; IDENTIFICATION; CARTILAGE; ELASTIN